Handbook of Damage Mechanics Nano to Macro Scale for Materials and Structures - Voyiadjis, George Z. (Springer New York : Imprint: Springer, 2015)
This authoritative reference provides comprehensive coverage of the topics of damage and healing mechanics. Computational modeling of constitutive equations is provided as well as solved examples in engineering applications. A wide range of materials that engineers may encounter are covered, including metals, composites, ceramics, polymers, biomaterials, and nanomaterials. The internationally recognized team of contributors employ a consistent and systematic approach, offering readers a user-friendly reference that is ideal for frequent consultation. Handbook of Damage Mechanics: Nano to Macro Scale for Materials and Structures is ideal for graduate students and faculty, researchers, and professionals in the fields of Mechanical Engineering, Civil Engineering, Aerospace Engineering, Materials Science, and Engineering Mechanics.